A Comparison of the Viewpoints of Clinical Educators and Students of the University of Social Welfare and Rehabilitation Sciences toward Clinical Training Status of Rehabilitation Disciplines in 201314 - Reza Kariminejad; Roshanak Vameghi; Kianoush Abdi; Enayatollah Bakhshi; Zeinab Mohammdzadeh (Kerman University of Medical Sciences, 2015)
Background & Objective: Clinical education courses are recognized as the heart of professional education because more than 50% of students time is spent in clinical environments Therefore qualifying in clinical skills requires an effective clinical learning environment Thus clinical education can be enriched through the consideration of clinical educators and students perspectives The aim of this study was to compare the viewpoints of clinical educators and students of the University of Social Welfare and Rehabilitation Sciences Tehran Iran toward the clinical education status of rehabilitation disciplines Methods: This study was a crosssectional study Based on the inclusion criteria and using convenience sampling method 54 clinical educators and 178 students were chosen from among clinical educators and students of orthopedics physiotherapy occupational therapy and speech therapy disciplines The participants completed valid and reliable clinical education questionnaires in the field of rehabilitation Results: A statistical difference was observed between clinical educators and students viewpoints in the area of "clinical learners" With regard to the academic degrees of clinical educators there was a statistically significant difference in the "evaluation area" With regard to the gender of clinical educators differences were observed in the area of "clinical learners" According to students academic disciplines with the exception of the field of "management" statistical differences were observed in other areas Conclusion: Clinical education courses in Rehabilitation Sciences must provide an effective clinical learning setting Moreover reviewing of management and evaluation of clinical education through appropriate evaluation criteria in order to improve the clinical education status is necessary